1992
DOI: 10.1161/01.cir.86.6.1800
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme inhibition restores cardiac and hormonal responses to volume overload in patients with dilated cardiomyopathy and mild heart failure.

Abstract: We conclude that pretreatment with the ACE inhibitor quinapril significantly improves compromised responses to acute isotonic volume overload in patients with dilated cardiomyopathy and mild heart failure. The favorable influence of ACE inhibition on cardiovascular and hormonal responses to volume expansion seems to be related to the cardiac unloading produced by this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…However, the ANP response to acute volume expansion is blunted in cardiac hypertrophy as well as heart failure (18,23,25). It is unclear whether the impaired ANP release in heart failure is a result of neurohormonal suppression or due to an inhibition of the release mechanism itself.…”
mentioning
confidence: 99%
“…However, the ANP response to acute volume expansion is blunted in cardiac hypertrophy as well as heart failure (18,23,25). It is unclear whether the impaired ANP release in heart failure is a result of neurohormonal suppression or due to an inhibition of the release mechanism itself.…”
mentioning
confidence: 99%
“…Indeed, the impaired ability to excrete ingested sodium is a key feature of patients with congestive HF [4,5]. Recent studies have demonstrated that renal sodium retention can occur in patients with asymptomatic LVD and mild HF [6][7][8], and in experimental HF, without increased activation of the RAAS [14]. It is difficult to elucidate mechanisms by which sodium and water retention occur in very early heart disease as most patients immediately receive (or have already received) treatment that affects the mechanisms being studied.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the pathophysiology of sodium and water retention in HF, particularly with regard to the time of onset of this abnormality during the course of the disease, remains inadequately studied. Volpe and co-workers [6][7][8] have reported that patients with asymptomatic LVD or mild HF clearly show abnormalities in renal sodium and water handling well before detectable changes in cardiac output. However, few studies have examined the response to chronic volume loading immediately post-MI.…”
Section: Introductionmentioning
confidence: 99%
“…In chronic heart failure, sympathetic activity is usually increased, causing systemic vasoconstriction via vascular c~-adrenoceptor and maintaining cardiac output via myocardial/~-receptors [8]. The preload reserve is also greatly limited in the failing heart [9]. In the presence of these abnormalities, a selective decrease in heart rate and cardiac contractility due to myocardial/~-receptor blockade could disclose a state of afterload mismatch, further decreasing cardiac output.…”
mentioning
confidence: 99%